PROBLEM APPROACH TO THE STUDY LITERARY SUBJECTS IN PEDAGOGICAL HIGH SCHOOL - Zhestkova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article describes a problematic approach in the study of literary disciplines in pedagogical high school. The success of problem-based learning is largely dependent on the correctness of methodical thinking university professors of all the amount of work on this or that discipline, as well as the following tasks: determination through theoretical and practical problems (macro-tasks) and specification of them in relation to each lecture (mikrozadachi), the definition of thematic content course, partitioning for information and illustrative presentation and selection of practical problems; Organization of finding solutions to problems (production and formulation of the problem, the creation of an independent activity of algorithms for solving problems of creative and exploratory nature); checking the degree of assimilation search techniques and evaluation of scientific and practical results, and comparative analysis of the expected results; analysis of the teacher of his work. Problem approach, implemented on a lecture or lab, requires active management of cognitive activity of students. The object of problem-based learning should be a part of the knowledge of the material, outlines the teacher and students learn.